Rehabilitasi Medik Pasien Pasca Stroke - Alma Nazelia Syafni (Jurnal Ilmiah Kesehatan Sandi Husada, 2020)
Background; stroke is one of the leading causes of death and disability worldwide. The stroke itself ranks second after heart disease as a cause of death worldwide in 2013. The mortality, morbidity, and disability rates in stroke patients increase every year. Stroke is a syndrome characterized by rapidly developing clinical symptoms and signs in the form of focal or global brain functional disorders lasting more than 24 hours (unless there is surgical intervention or death), which is not caused by causes other than vascular causes. Conclusion; treatment of stroke patients is always based on the factors causing the stroke itself. Medical rehabilitation is an effort made to restore the patient's physical ability to its previous state before being sick in the shortest possible time. Medical rehabilitation includes three things, namely, medical, social, and vocational rehabilitation